Stumbling Reactions in Partial Gravity – Neuromechanics of Compensatory Postural Responses and Inter-Limb Coordination During Perturbation of Human Stance - Ritzmann, Ramona; Freyler, Kathrin; Helm, Michael; Holubarsch, Janek; Gollhofer, Albert (Frontiers in Physiology, 2019)
Spontaneous changes in gravity play a significant role in interplanetary space missions. To preserve the astronauts’ capability to execute mission-critical tasks and reduce the risk of injury in transit and on planetary surfaces, a comprehensive understanding of the neuromuscular control of postural responses after balance deterioration in hypo- or hyper-gravity conditions is essential. Therefore, this study aimed to evaluate the effect of gravitational variation on postural adjustments in response to perturbations. Postural set was manipulated by randomly providing unilateral, bilateral or split perturbations which require balance corrections to restore postural stability. In six subjects, postural reactions were recorded after anterior and posterior surface impulses for progressively increased gravitational conditions spanning from 0.25 to 1.75 g. Ankle and knee joint kinematics and electromyographic activity (EMG) of eight leg muscles were recorded prior (PRE) and after perturbation onset. Onset latencies and muscle activities in the short-, medium- and long-latency responses (SLR, MLR, LLR) were assessed. Results demonstrate an increased muscle activity (p<0.05) and co-contraction in the lower extremities (p<0.05) prior to perturbation in hypo- and hyper-gravity. After perturbation, reduced muscle onset latencies (p<0.05) and increased muscle activations in the MLR and LLR (p<0.05), concomitant with an increased co-contraction in the SLR, were manifested with a progressive rise in gravity. Ankle and knee joint deflections remained unaffected, whereas angular velocities increased (p<0.05) with increasing gravitation. Effects were more pronounced in bi- compared to unilateral or split perturbations (p<0.05). Neuro-mechanical adaptations to gravity were more distinct and muscle onset latencies were shorter in the displaced compared to the non-displaced leg. In conclusion, the timing and magnitude of postural reflexes involved in stabilization of bipedal stance are gravity-dependent. The approximately linear relationship between gravity and impulse-directed EMG amplitudes or muscle onset latencies after perturbation indicates that the central nervous system correctly predicts the level of gravity. Moreover, it accurately governs contractions in the antigravity musculature to counterbalance the gravitational pull and to regain upright posture after its disturbance. Importantly, unilateral displacements evoked fast reflex responses in the synergistic muscles of the non-displaced contralateral leg suggesting a synchronized inter-limb coordination mediated by spinal circuitries.